2013
DOI: 10.1007/s00482-013-1320-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental occupation on access to specialised treatment for paediatric chronic pain

Abstract: The association between travel distance and parental occupational skill level suggests that there is social injustice due to access barriers based on socioeconomic deprivation and education. An increase in the number of health care facilities for chronic pain in children would be a first step in rectifying this injustice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Less use of secondary care despite higher clinical need and use of primary care in groups of low SES have been documented in other health contexts 3–5. A study from a children's pain centre in Germany reported similar findings 23. Interestingly, they used a different measure of SES (individual-level parental occupational skill) finding that children whose parents had higher occupational skill levels were more likely to have travelled from outside the centre's 80% catchment area, and that the 80% catchment area increased with increasing parental skill level.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Less use of secondary care despite higher clinical need and use of primary care in groups of low SES have been documented in other health contexts 3–5. A study from a children's pain centre in Germany reported similar findings 23. Interestingly, they used a different measure of SES (individual-level parental occupational skill) finding that children whose parents had higher occupational skill levels were more likely to have travelled from outside the centre's 80% catchment area, and that the 80% catchment area increased with increasing parental skill level.…”
Section: Discussionmentioning
confidence: 63%
“…We used distance to the study centre rather than travel time. Although it has been shown that distance and travel time are highly correlated (r=0.98),23 for patients living in some areas, distance and travel time will not always correspond. Finally, the IMD does not provide data on deprived individuals, but deprived areas; individual-level socioeconomic data would be needed to construct more revealing statistical models.…”
Section: Discussionmentioning
confidence: 98%
“…Before presenting to specialized pediatric pain treatment centers, patients undergo a substantial number of medical visits and pain-related hospital stays [2,11,17,18]. Furthermore, other barriers to accessing specialized pain care exist, such as availability of care [19,20,21] and socioeconomic status [19,20]. A lack of understanding in society and among friends, family or even primary care physicians due to the invisible nature of pain may also present a barrier to specialized care [22].…”
Section: Introductionmentioning
confidence: 99%
“…We found no evidence for attending a physician for pain-treatment depending on SES. In contrast to this access to specialized treatments seems to depend on parental SES (Wager et al, 2013b). In studies with adult chronic pain patients, results concerning the association between health care utilization due to chronic pain and socioeconomic status are conflicting.…”
Section: Preprintsmentioning
confidence: 90%
“…Over the last ten years a number of studies aimed to describe those children who not only have recurrent pain but also visit physicians or specialized treatment centers (Peng et al, 2007;Wager et al, 2013b). Factors associated with physician visits due to recurrent pain may be relevant to better understand children seeking professional help, and shape the health care system.…”
Section: Introductionmentioning
confidence: 99%